KONSEP ADIL POLIGAMI DALAM PANDANGAN M. QURAISH SHIHAB DAN SITI MUSDAH MULIA - Wahyuninto, Liza (UIN Fatmawati Sukarno Bengkulu, 2018)
The purpose of this study is to first describe the views of Quraish Shihab and Siti Musdah gloriously looking at polygamy verses, the practice of polygamy of the Prophet and the fair terms of polygamy, secondly to describe a fair concept in polygamy according to Quraish Shihab and Siti Musdah Mulia, third to describe the legal arguments of Quraish Shihab and Siti Musdah His Majesty of fair concepts in polygamy. This research method is literature research using qualitative description research method. Based on the results of research and discussion can be drawn the following conclusions: First, in understand- ing the verses of polygamy, Quraish Shihab argues that based on the demands of fair treatment of orphans as an accentuation of this paragraph, the context of emphasis on the command to be fair and polygamy verses do not make regulations about po- lygamy, because it has been known and implemented by adherents of various shari’a religion and community traditions before the decline of this verse. Siti Musdah Mulia sees that of the whole verse of marriage, First, polygamy is contrary to the principle and purpose of marriage of Islam. Secondly, QS. An-Nisa verse 3 does not speak in the context of polygamous justification, but in the context of protection for orphans and women from injustice behavior. Second, M. Quraish Shihab gives insight into the practice of polygamy of the Prophet (s), nor can it be said that Rasulullah SAW marries more than one, and such marriages should be imitated, because not all what is done by the Prophet needs to be imitated.Sedangkan Siti Musdah Mulia, the as- sumption that polygamy Prophet is a sunnah that can be made hujjah. Thirdly, Justice of polygamy according to M. Quraish Shihab is fair in the field of immaterial (love). Siti Musdah Mulia gives the view that there are two main points in looking at the fair concept in polygamy. First, the just is meant not only in terms of material things such as livelihood but also in the immate- rial matter, namely the tendency of love and compassion. Second, fair criteria covering two aspects in it, impossible or hardly anyone can afford to fulfill the prophet SAW